1974
DOI: 10.1113/jphysiol.1974.sp010718
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of nerve membrane depolarization caused by grayanotoxin I

Abstract: SUMMARY1. The mechanism of depolarization of squid axon membranes caused by grayanotoxin I has been studied by means of internal perfusion and voltage clamp techniques.2. The depolarization induced by either internal or external application of grayanotoxin I was reversed by decreasing the external sodium concentration from 449 to 1 mmw.3. No depolarization was observed when both external and internal media were devoid of sodium ions, indicating that the depolarization by grayanotoxin I in normal media is due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
1

Year Published

1977
1977
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(49 citation statements)
references
References 28 publications
1
47
1
Order By: Relevance
“…Like veratridine (Ito et al, 1978;, scorpion venom and grayanotoxin I plus scorpion venom caused an increase in the catecholamine output from the perfused adrenal gland in the presence of atropine and hexamethonium and the effects were blocked by TTX or by deprivation of extracellular Na+ or Ca2+ ions. These neurotoxins are known to act on TTX-sensitive Na+ channels in various excitable cells (Narahashi et al, 1972;Ohta et al, 1973;Narahashi & Seyama 1974;Starkus & Narahashi 1978), although the mechanism of action is somewhat different. In addition, these toxins failed to depolarize the nerve axons in the absence of or in low extracellular Na+ (Adam et al, 1966;Narahashi & Seyama 1974;Starkus & Narahashi 1978).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Like veratridine (Ito et al, 1978;, scorpion venom and grayanotoxin I plus scorpion venom caused an increase in the catecholamine output from the perfused adrenal gland in the presence of atropine and hexamethonium and the effects were blocked by TTX or by deprivation of extracellular Na+ or Ca2+ ions. These neurotoxins are known to act on TTX-sensitive Na+ channels in various excitable cells (Narahashi et al, 1972;Ohta et al, 1973;Narahashi & Seyama 1974;Starkus & Narahashi 1978), although the mechanism of action is somewhat different. In addition, these toxins failed to depolarize the nerve axons in the absence of or in low extracellular Na+ (Adam et al, 1966;Narahashi & Seyama 1974;Starkus & Narahashi 1978).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibitory effect of tetrodotoxin on catecholamine secretion induced by scorpion venom and grayanotoxin I It is reported that either TTX or reduction of extracellular Na+ ions abolishes the depolarization or the prolongation of Na+ current induced by grayanotoxin I and/or scorpion venom in various excitable cells (Adam et al, 1966;Narahashi et al, 1972;Narahashi & Seyama 1974;Starkus & Narahashi 1978). Scorpion toxin-induced release of noradrenaline from peripheral adrenergic neurones is also inhibited by Adrenal glands were first perfused with Ca2 +-free solution containing Mg2 + 2 mM for 25 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Grayanotoxin binds the voltage-dependent sodium (Na) channel of excitable cells from the inside of the cell [16] in its open state [17]. The receptor consists of the S6 transmembrane segments of four homologous domains facing the ionconducting pore [18].…”
Section: Mad Honey Is Different From Common Commercial Honeymentioning
confidence: 99%
“…In order to see whether the antagonistic effect of high concentrations of K+ was due simply to the reduced membrane potential, the effect of grayanotoxin I (Seyama, 1970;Narahashi & Seyama, 1974), was studied. In confirmation of previous reports, grayanotoxin I at 5 gig/ml depolarized the rat diaphragm muscle from -83 mV to about -50 mV in about 20 min and the effect did not increase.…”
Section: Effect Of Low Cl-mentioning
confidence: 99%